What is The Future of Nation State? Case Study of Pakistan - Shaloom Naeem; Sharyl Naeem (International Journal on Orange Technologies, 2021)
This paper discussed about the emergence of the nation-state, its historical background. This research mainly focused on the Renan philosophical concepts about the nation and nation state. According to Renan view, the soul with a common past and experience and the acceptance of its legacy is something which constructs a nation. This research enlightened the study of Pakistan as a nation, apart from Muslim nationalism the moderate political leaders have tried to develop this notion of oneness on the basis of the common struggle to receive this land and the admiration of the struggle by coming generations and accepting and embracing that legacy by new generations. This paper not only studied the Renan political though about nation state but also explained the Geertz concept of Sovereignty, Wimplemann philosophical views about working of state institutions, Kachtan thoughts on ethnicity, division and conflicts of people on the basis of ethnicity, Habermas and Bennett ideas on civil disobedience. It has been analyzed that the future of nation state is shady if it will be left on its own; it is the different things which artificially keep the sense of nation and nation state alive.